De aluno a professor - o início da construção profissional de um professor de educação física - Leandro Miguel Araujo da Silva (2022)
The practice of supervised teaching is paramount in the process of the professional training of a physical education teacher. The fact that one is accompanied by professionals in the area on a daily school context by the collaborating teacher and in the university context by the supervisor teacher, makes the experiences more enriching and profitable. In this document I will write about my journey throughout this year of internship, where I will frame the practice, talk about how I implemented the knowledge acquired from the first year of graduation to the present day, as well as the difficulties experienced (for example, in planning, since the school had a distributed practice structure) and learning carried out (for example, management capacity at the level of multi-activity classes) throughout the school placement. This was undoubtedly a year of a fresh start in view of the pandemic context of the recent past. This context allowed a fully face-to-face immersion in order to engage students in the process throughout the year, permitting the adoption of the best strategies for knowledge acquisition. The reality of a different way of approaching teaching and distributed practice will also be an important point along the way. With the purpose of developing my pedagogical practice and improving my ability to perform the teacher's role, I felt, in this school placement, the need to study about the knowledge of content, specifically content specialized knowledge (developed in the area 3). I ended with the feeling of fulfilled duty and willing to turn these experiences into my routine. Being a teacher proved to be something extremely enriching and conducive to a feeling of personal and professional fulfilment.